ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN KAUR - Muhamad Zuhri; Ahmad Soleh (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
One positive impact of the implementation of regional autonomy is the expansion of provincial and district / city that almost occurred throughout Indonesia. One area is the result of the expansion area Kaur regency in Bengkulu Province. As a new district that grows future regional autonomy, Kaur District has the authority to manage their own regions. The purpose of this study was to determine the Financial Performance of the District Government Kaur. Data collection method used is documentation. While the method of analysis using quantitative methods using financial ratios. Financial Performance of the District Government Kaur years 2001-2014 when viewed from the Regional Financial Independence Ratio is relatively low once (an average of 2.44% per year). Effectiveness Ratio  PAD is known that the effectiveness of Kaur regency in 2011, 2013 and 2014 runs Ineffective indicated by the value ratio between 75% -89%, but in 2012 went very effective with a ratio reached 107.3%. Activity Ratio of the ratio of Operating Expenditure quite well that the value ratio between 50% -100% or the average value of 76.7% per year, while the ratio of Capital Expenditure classified as not good because it has value ratio is less than 50% or the average value -rata year by 23.2% per year). Growth in revenue (PAD) Kaur District has increased from year to year, but the growth was relatively moderate growth with an annual average value of 45.22% per year. Key Words: Financial performance, Ratio of Regional Financial Independence, Effectiveness Ratio, Activity Ratio, Growth Ratio, Kabupaten Kaur.